2013
DOI: 10.3354/meps10100
|View full text |Cite
|
Sign up to set email alerts
|

Seal scarers as a tool to deter harbour porpoises from offshore construction sites

Abstract: Offshore pile driving, e.g. during wind farm construction, produces substantial noise emissions into the water column, which may harm marine mammals. Therefore, it is common practice to attempt to deter the mammals out of potential danger zones beforehand. Seal scarers are commonly used as a deterrent for harbour porpoises in spite of a lack of clear evidence in support of their effectiveness. We investigated the responses of harbour porpoises to a Lofitech seal scarer by conducting visual observations in conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 18 publications
6
23
0
1
Order By: Relevance
“…The low‐frequency components of the signal measured at 20 m distance did not significantly exceed the detection threshold of the farmed fish (see Hawkins & Johnstone, , for audiogram). In previous studies harbour porpoises have been shown to respond to sounds at a relatively low RL at frequencies between 8 and 80 kHz (Johnston, ; Kastelein et al ., ; Brandt et al ., ). Since harbour porpoises did not respond to our playbacks, we feel confident that results would be similar with other odontocete species, such as bottlenose dolphins Tursiops truncatus or long‐finned pilot whales Globicephala melas , which have a broadly similar hearing sensitivity to harbour porpoises but generally seem to tolerate noise much better (Cox et al ., ; Antunes et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The low‐frequency components of the signal measured at 20 m distance did not significantly exceed the detection threshold of the farmed fish (see Hawkins & Johnstone, , for audiogram). In previous studies harbour porpoises have been shown to respond to sounds at a relatively low RL at frequencies between 8 and 80 kHz (Johnston, ; Kastelein et al ., ; Brandt et al ., ). Since harbour porpoises did not respond to our playbacks, we feel confident that results would be similar with other odontocete species, such as bottlenose dolphins Tursiops truncatus or long‐finned pilot whales Globicephala melas , which have a broadly similar hearing sensitivity to harbour porpoises but generally seem to tolerate noise much better (Cox et al ., ; Antunes et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Seal scarers have been shown to effectively displace porpoises several kilometres (Brandt et al 2012(Brandt et al , 2013 and the cumulated noise exposure from pile-driving noise is therefore substantially reduced, minimizing the number of porpoises at risk of developing TTS. The results from DanTysk indicate that the seal scarer indeed deterred porpoises, up to a distance of at least 12 km and perhaps even 18 km from the pile driving, seen as a significant reduction in %PPM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic deterrent devices are known to have far‐reaching effects in the absence of piling noise (Brandt et al. , b). Efforts to optimize assessment and mitigation measures during anticipated increases in coastal construction activity (Bulleri and Chapman ) therefore require better understanding of the relative influence of different high‐frequency (ADD) and lower‐frequency piling noise sources on behavioral responses.…”
Section: Discussionmentioning
confidence: 99%